"Ô levanta nego, cativeiro se acabou" : experiências de libertos em Sergipe durante o pós-abolição (1888-1900) - Souza Neto, Edvaldo Alves de (2016)
It still remains in the story of Sergipe, mainly in the capital Aracaju, many question marks about what happened with the old slaves and their descendents right after the abolition of the captivities in may 13th of 1888 with the signature of the Áurea law. To other places in Brazil, with the creation of a discussion group about the period after the abolition, such discussions attracted many researchers, reviewing old propositions and boosting new studies in a way that contributed to the configuration of a promising picture. The goal of this research, through the social story, mainly to theoretical reference developed by E. P. Thompson (1997; 1998; 2001), it brought the referred debate to the historical context of aracaju, identifying and analyzing individual and colective of old slaves and their descendents trajectories, expectations around liberty, the struggles for the extension of the rights, the ways of the reception and celebration of the good news of the abolition, including the social relation developed by these characters of the scenery of Sergipe, mainly in the capital Aracaju at the end of XIX. Therefore, the research is divided in three moments. In the first chapter we are going to analyze the space of Aracaju, investigating the limits of Aracaju, locating its released population and analyzing how they expressed their way of feeling, thinking and acting in the everyday life of the city. In the second chapter we are going to exam the way which the different social sectors received the good news of the abolition and which impacts caused every day of the countryside property and in the constitution of the new social relation between the lords and their released slaves. Lastly, verifying the achievements and aflitions of the freed persons in Sergipe in their everyday fights for home, work, leisure and political conception. We consulted judicial documents, newspapers from Sergipe in that period, maps, census, correspondences, novels, chronicles and memory.